Four-Year Trends in Cardiometabolic Risk Factors according to Baseline Abdominal Obesity Status in West-African Adults: The Benin Study - Charles Sossa; Hélène Delisle; Victoire Agueh; Michel Makoutodé; Benjamin Fayomi (Journal of Obesity)
The study examined whether abdominal obesity (AO) according to waist circumference was associated with more unfavourable changes in other cardiometabolic risk (CMR) factors in sub-Saharan Africans. The study included 541 randomly selected and apparently healthy subjects (50% women) aged 25–60 years. Complete data at baseline, 24, and 48 months later was available in 366 subjects. AO was associated with higher CMR at baseline and over the follow-up period, except for high blood pressure. A significantly higher incidence of high ratio of total cholesterol : HDL-cholesterol (TC/HDL-C) was associated with AO. Controlling for WC changes, age, baseline diet, and lifestyles, the relative risk (RR) of low HDL-C and high TC/HDL-C was 3.2 (95% CI 1.06–9.61) and 7.4 (95% CI 2.01–25.79), respectively, in AO men; the RR was not significant in women. Over a four-year period, AO therefore appeared associated with an adverse evolution of cholesterolemia in the study population.